Digital Entrepreneurship Characteristics and Challenges in Building Technology-Based Businesses - Rahidun; Alrizon (Jurnal Transformasi Digital dalam Ekonomi, Bisnis, dan Manajemen, 2025)
Digital entrepreneurship has become a key pillar in the development of the global economy, along with rapid technological advances. This study aims to explore the key characteristics required to build a technology-based business as well as the challenges faced by digital entrepreneurs. Key characteristics identified include adaptability to technological change, digital and data literacy, as well as user experience orientation and the application of growth hacking. However, despite great opportunities, challenges such as intense competition, limited capital and infrastructure, as well as issues related to data security and inadequate regulations, pose significant obstacles. The research also highlights the importance of utilizing advanced technologies such as AI, cloud computing, and big data, as well as the need for collaboration within the startup ecosystem, venture capital funding, and business incubators. In addition, building personal branding and digital communities are important factors in expanding market reach and increasing consumer trust. This study suggests that digital entrepreneurs should continue to develop their skills in adapting and utilizing technology, and suggests that policymakers should create regulations that are more supportive of digital business development. On the other hand, further research on the role of the startup ecosystem and the impact of new technologies on digital entrepreneurship is needed to enrich understanding in this field.